PENGARUH OZON TERHADAP HUJAN ASAM DI BANDUNG - Tuti Budiwati; - Sumaryati; Iis Sofiati; Tuti Mulyani HW; M. Pariyatmo (Lembaga Penerbangan dan Antariksa Nasional, 2006)
The monthly of concentration of surface ozone at Dago (north Bandung) from January 2001 to June 2003 of 38.30 μg/m3. This value is higher than other four stations, Cisaranten Wetan and Aria Graha (East Bandung), Batununggal Indah (South Bandung) and Tegallega (Central Bandung) within variations 35.26-36.23 μg/m3. While SO2, NO2 gases, SO42-, NO3-, NH42+ ions, and pH of rainwater are measured at five locations, i.e. Cipedes (West Bandung), Martadinata (East Bandung), Dago (North Bandung), Kopo (South Bandung) and Kebon Kalap (Central Bandung) from August 2000-May 2003. The worst condition of acid rain was found at Cipedes with value of 5.09. This condition means that locations have been affected by acid rain in August 2000 - May 2003, because the value of pH less than 5.60 (the threshold of acid rain). Other locations such as Martadinata, Kebon Kalapa, and Kopo have average value of pH of 5.75, 5.95, and 6.00, respectively. While Dago which represents cleanest region of five locations in Bandung has average of pH of 6.06. The existence of zone have not influenced yet the deposition of acid rain in Bandung in general, especially at Dago, if we see the biggest value of correlation coefficient on that region of 0.64. The influence of ozone is more dominant to SO2 compared to NO2 based on acid deposition formed. The pollutant of SO2, No2 gases, and aerosol from the local source influences on concentration of sulfate and nitrate ions which have the important role on acid rain.